2020
DOI: 10.1002/ppap.201900270
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial effects and mechanism of air plasma‐activated water on Staphylococcus aureus biofilm

Abstract: The deactivation effects and mechanism of plasma‐activated water (PAW) against Staphylococcus aureus biofilm and the inhibitory effect on the biofilm regrowth capacity for the surviving S. aureus post PAW treatment were investigated in vitro. Systematic measurements on bacterial cultivability, metabolic capacity, membrane integrity and intracellular reactive oxygen species (ROS) concentration under two different experimental categories were carried out after PAW treatment. Considerable deactivation effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 58 publications
1
53
0
Order By: Relevance
“…But biofilms by nature are complex biomaterials, (i) the biofilm architecture and (ii) its composition may limit penetration of reactive species into the biofilm matrix. Many previous studies demonstrated, that increasing treatment time and contact period could improve plasma inactivation efficacy against bacterial biofilm [30][31][32][33] . However, in this study PAW was combined with airborne acoustic ultrasound technology in order to obtain higher inactivation efficacies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But biofilms by nature are complex biomaterials, (i) the biofilm architecture and (ii) its composition may limit penetration of reactive species into the biofilm matrix. Many previous studies demonstrated, that increasing treatment time and contact period could improve plasma inactivation efficacy against bacterial biofilm [30][31][32][33] . However, in this study PAW was combined with airborne acoustic ultrasound technology in order to obtain higher inactivation efficacies.…”
Section: Resultsmentioning
confidence: 99%
“…While the biofilm is dispersing the remaining cells are exposed to RONS and become more susceptible to be inactivated by PAW. The reactive species generated in PAW not only affects the cell membrane integrity but also penetrate into membrane channels and provoke reactive oxygen species (ROS) production endogenously which account for the intracellular ROS accumulation inside the cell 31 , 38 . Studies by Lukes et al 39 and Xu et al 31 also demonstrated that RONS interact with intracellular components (DNAs, proteins, lipids) and influence its metabolic responses in microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of PAW on biofilms have also been explored. A study by Xu et al [ 63 ] indicated that both the plasma inducement time and the plasma treatment time could affect the bacterial cells in their ability to generate biofilms. Apart from more than 5 log 10 CFU/unit reduction of S. aureus cells in the biofilm, the regrowth capacity of the surviving cells was reduced by 30% as compared with the untreated cells [ 63 ].…”
Section: The Effect Of Paw On Bacterial Inactivationmentioning
confidence: 99%
“…A study by Xu et al [ 63 ] indicated that both the plasma inducement time and the plasma treatment time could affect the bacterial cells in their ability to generate biofilms. Apart from more than 5 log 10 CFU/unit reduction of S. aureus cells in the biofilm, the regrowth capacity of the surviving cells was reduced by 30% as compared with the untreated cells [ 63 ]. This effect is postulated as a result of regulation of genes ( SarA , IcaA , SigB , Rbf , LuxS ) involved in biofilm formation, especially in response to disinfectants such as hydrogen peroxide.…”
Section: The Effect Of Paw On Bacterial Inactivationmentioning
confidence: 99%